Roots of Violence in Indonesia - Colombijn, Freek, Lindblad, J. Thomas (ISEAS, 2002)
Jakarta, Sambas, Poso, the Moluccas, West Papua. These simple, geographical name have recenly obtained strong assoiations with mass killing, just as Aceh and East Timor, where large-scale violence has flared up again.